Incidencia de los niveles de pectina y lactosuero en la calidad del manjar de leche - Torres Muñoz, Gema Liseth (2016)
This research was based on the use of whey as a partial substitute of milk in the preparation of delicacy with addition of pectin as a stabilizer, this was an experimental completely randomized design which provided with a result of 9 treatments with 3 replications of each, where the incidence of pectin levels were proved (0.5%, 1% and 1.5%) and whey (30%) 40% and 50%) in the milk delicacy quality, the methodology used to evaluate physicochemical parameters were those set on the NTE INEN 700:2011, which expresses the test method for loss by heating, total solid and total sugars; in addition, the level of acceptability of the final product by using a test system of sensory analysis was determined. The data were subjected to the statistical program IBM SPSS free version and it was established that the best treatment was T2 with percentage of 30% of whey and 1% of pectin, which showed 16.79% in losses by heating; 72.71% of total solids and 49.08% of total sugar, the tabulation of data of the sensory analysis displayed T7 composed of 50% whey and 0.5% of pectin, which was the one with the greater acceptability by the panelists, what is more, it was possible to demonstrate when conducting the sensory analysis that all treatments were acceptable, so it is concluded that whey and the levels of study appear to positively influence the organoleptic characteristics of the delicacy.